Penerapan Pajak Penghasilan Pasal 23 dan Perlakuan Akuntansi Atas Jasa Sewa Alat Berat Pada PT Samudera Mulia Abadi - Kolang, Engelina Aprilia Fergenia; Sondakh, Jullie; Pangerapan, Sonny (Universitas Sam Ratulangi, 2022)
The income tax has an important role as one of the state revenues. Article 23 of Income Tax is one of the state revenues that has a large contribution. This research was conducted at the mining contractors company, PT Samudera Mulia Abadi. This research aimed to evaluate the application of Income Tax in Article 23 on heavy equipment rental services at PT Samudera Mulia Abadi whether it was related to the Law Number 36 of 2008, Paragraph 1(c). This research used a qualitative method with a descriptive approach. The results revealed that the calculation and reporting process of PT Samudera Mulia Abadi was related to the Law Number 36 of 2008 concerning Income Tax. In addition, this company records based on the accounting standards.